2017
DOI: 10.1111/dar.12624
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption among first‐ and second‐generation immigrant and native adolescents in 23 countries: Testing the importance of origin and receiving country alcohol prevalence rates

Abstract: Our results suggest differences in lifetime frequencies of alcohol use and drunkenness between natives and first- and second-generation immigrant adolescents. Origin country APCC and HED seem to affect immigrant adolescents' alcohol consumption differently than receiving country APCC and HED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…The fact that levels of alcohol use among Ethiopian adolescents were not significantly higher than among Israeli born adolescents may challenge former studies pointing to higher levels of drinking among adolescent immigrants ( Walsh et al, 2014 ). However, findings are in line with recent research showing that levels of drunkenness and heavy episodic drinking among adolescents may be related more strongly to levels of drinking in the country of origin ( Barsties et al, 2017 ). Levels of alcohol use among the Ethiopian Jewish community were very low ( Kebede et al, 2005 ; Grisaro and Witztum, 2012 ).…”
Section: Discussionsupporting
confidence: 91%
“…The fact that levels of alcohol use among Ethiopian adolescents were not significantly higher than among Israeli born adolescents may challenge former studies pointing to higher levels of drinking among adolescent immigrants ( Walsh et al, 2014 ). However, findings are in line with recent research showing that levels of drunkenness and heavy episodic drinking among adolescents may be related more strongly to levels of drinking in the country of origin ( Barsties et al, 2017 ). Levels of alcohol use among the Ethiopian Jewish community were very low ( Kebede et al, 2005 ; Grisaro and Witztum, 2012 ).…”
Section: Discussionsupporting
confidence: 91%
“…That immigrant youth tend to drink alcohol less frequently than their native counterparts was also found in a large study among 13‐ to 15‐year‐olds in 23 receiving countries coming from over 130 origin countries . The authors argue that this is due to the cultural norms and values on alcohol consumption in the country of origin, which tend to be—at least among first generation immigrants—more important determinants of immigrant adolescent alcohol consumption than those in the receiving country.…”
Section: Effects Of Immigration Acculturation‐related Stress Socio‐mentioning
confidence: 68%
“…Barsties et al . also argue that the high rates of drunkenness found among immigrant youth can be a sign of immigration‐related difficulties and stressors, which may also be part and parcel of a disadvantageous socio‐economic situation.…”
Section: Effects Of Immigration Acculturation‐related Stress Socio‐mentioning
confidence: 99%
“…Transnationalism theory suggests that substance use norms among first-as well as second-generation immigrants might still be informed by those prevalent in their country of origin [43]. In support of this hypothesis, some studies found that less widespread alcohol use in the country of origin was associated with less alcohol consumption among immigrant adolescents [43,44]. Similarly, the lower prevalence of current smoking among adolescents of Portuguese descent in Luxembourg when compared to native Luxembourgish adolescents might be linked to the lower prevalence of smoking among adolescents in Portugal when compared to their counterparts in Luxembourg [24].…”
Section: Discussionmentioning
confidence: 99%